An Explorative Study on Social Media Blocking in Indonesia - Faiq Wildana (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
The internet access blocking to the highly used Social Media platform was a new Indonesian government occurrence. Even though it was for a good purpose and did not block full access, it triggered many protests toward the Government. This study aims to get Indonesian's perspective toward Social Media blocking regarding the reasons, the Government's action, and their readiness if there is no Social Media blocking. Convenience survey sampling was conducted to acquire quantitative and qualitative data among Indonesians. The results indicate that Indonesian favored Social Media blocking if it has clear reasons and not ready if the Government held none of such action. They also demand the Government to provide notification, duration estimation, and guaranteed access to mainstream media. However, they object to Social Media blocking if the motives are regarding freedom of politics, religions, and sexual orientation issues.